PENGARUH PENERAPAN APLIKASI FAKTUR PAJAK ELEKTRONIK (E-FAKTUR) TERHADAP TINGKAT KEPATUHAN WAJIB PAJAK - Novita Sari (Journal of Accounting and Management, 2025)
An electronic tax invoice, hereinafter referred to as an e-Invoice, is a tax invoice created through an application or electronic system specified and/or provided by the Directorate General of Taxes. The implementation of e-Invoices can encourage better self-assessment. Therefore, the researcher intends to determine the level of taxpayer compliance in reporting Value Added Tax using the latest application, the electronic tax invoice (e-Invoice), at the Pratama Tax Office (KPP) in Kebon Jeruk Satu, West Jakarta. This study uses descriptive quantitative research. This data is derived from respondents' answers to a questionnaire administered by the researcher. The data were then analyzed using a Likert scale, allowing for further processing using SPSS 24 for Windows. The independent variable is the Electronic Tax Invoice (E-Invoice) application, and the dependent variable is taxpayer compliance. E-Invoice is an application for creating electronic tax invoices or proof of VAT collection electronically. The introduction of e-Invoices is expected to improve taxpayer compliance. Based on a simple analysis, this study found that the simultaneous implementation of e-Invoices with variable X significantly impacts Y (taxpayer compliance). Partially (t-test) results showed that e-Invoice application influences taxpayer compliance levels.